Do Lomer Dislocations Spoil High Performance of mc-Si Solar Cells?. (August 2015) - Bauer, Jan; Hähnel, Angelika; Blumtritt, Horst; Deniz, Hakan; Zuschlag, Annika; Breitenstein, Otwin
Abstract: Material induced inherent efficiency losses of multicrystalline silicon solar cells have been investigated across all scales from the solar cell down to the atomic structure of the responsible crystallographic defects. Material inherent efficiency losses can be attributed to local increased dark current, which is found at recombination active small angle grain boundaries and accounts to several per-cent absolute. Aone-to-one correlation between the density of Lomer dislocations and the strength of the recombination activity of small angle grain boundaries is found by electron-beam induced current measurements and scanning transmission electron microscope investigations. The increased recombination activity of Lomer dislocations is attributed to their immobile nature, which favors contamination by impurities.